Conducting terrorism field research a guide - Dolnik, Adam (Contemporary terrorism series, 2013)
This book offers a detailed and practically oriented guide to the challenges of conducting terrorist fieldwork. The past decade has seen an explosion of research into terrorism. However, field research on terrorism has traditionally been surrounded by many myths, and has been called anything from "necessary" and "crucial" to "dangerous", "unethical" and "impossible". While there is an increasing interest among terrorism specialists in conducting such research, there is no single volume providing prospective field researchers with a guideline to such work.